Effect of the photothermal Moore-Gibson-Thomson model on a rotating viscoelastic continuum body with a cylindrical hole due to the fractional Kelvin-Voigt model - Alfadil, Husam; Abouelregal, Ahmed E.; Civalek, O.; Öztop, Hakan Fehmi (Indian Assoc Cultivation Science, 2023)
According to recent research, the theoretical consequences of viscoelastic materials may be adequately described using fractional calculus. A novel model for the fractional time derivative of the Kelvin-Voigt type of viscoelastic semiconductor material has been provided in this study. The Atangana and Baleanu (AB) fractional derivatives operator is utilized, which employs the generalized Mittag-Leffler function as a nonlocal and non-singular kernel and respects all features of fractional derivatives. The Moore-Gibson-Thompson (MGT) photothermal heat transfer model has also been considered to explain the mechanism of photosensitive heat transfer and the interplay between plasma, elastic, and heat signals. This fractional model is used to explore thermal and photoacoustic interactions when an infinite viscoelastic rotating material with a circular cylindrical hole is exposed to a time-dependent variable heat in the presence of an axial constant magnetic field. The solutions of photothermal field variables are obtained using Laplace transform methods, and the technique of Fourier series expansions is applied to obtain the inversions. Results have been listed to examine how the fractional-order and mechanical viscoelastic relaxation parameters affect different photo-thermoelastic variables that have physical meaning.
Keywords: Photo-thermo-viscoelasticity; Semiconductor; Rotation; Atangana-Baleanu operator